Studi Perbandingan Pengaturan tentang Pengecualian Industri Pertanian Terhadap Berlakunya Hukum Persaingan Usaha - Siti Anisah (Jurnal Hukum IUS QUIA IUSTUM, 2012)
The research is aimed at finding out whether the exemption for agricultural industries in the competition laws in Unites States of America and European Union is fully or partially granted. In addition, the study examines whether the competition law in Indonesia also regulates exemption for agricultural industries. The research method is normative juridical with a legal comparison approach. The result shows that the exemption for agricultural industries in the United States of America mentioned in the antitrust law was regulated by the Congress through Clayton Act 1916 and confirmed in Capper-Volstead Act 1922. In European Union, the exemption is regulated in the Treaty Establishing the European Community. The regulations in the United States and European Union are the same, in which farmers are allowed to establish agricultural cooperatives that aim to meet the needs of its members, such as collective processing, preparation for markets, merchants, and marketing. Although Indonesia does not have a specific law for exemption, several stipulations in Article 50 and 51 of Law No. 5 Year 1999 can be interpreted as exemption for agricultural industries in the competition law.